The handbook of development communication and social change - Obregon, Rafael; Tufte, Thomas; Wilkins, Karin Gwinn 1962- (Chichester, England Wiley Blackwell, 2014)
"This Handbook of Development Communication and Social Change offers a valuable resource for advocates, scholars, and communities engaged in long-term and comprehensive struggles for social justice. This book fills a critical niche by offering a comprehensive framework in a growing area of research and action, as social movements and organizations make strategic use of communication technologies and processes in a complex world of dominant global industries and oppressive political regimes ... This work integrates the interests of many of the International Association for Media and Communication Research (IAMCR) sections, including that of participatory communication, health communication, community communication, communication policy and technology, gender and communication, political communication, and political economy"--
Introduction; Part I: Communicating Development and Social Change; 1: Development Communication and Social Change in Historical Context; 2: Globalization and Development; 3: Political Economy of Development; 4: Advocacy Communication; 5: Equality and Human Rights; 6: Public Health; 7: Indigenous Communication: From Multiculturalism to Interculturality; 8: Communication, Development, and the Natural Environment; 9: Emerging Issues in Communicating Development and Social Change; Part II: Developing Strategic Communication for Social Change; 10: The Strategic Politics of Participatory Communication; 11: Rethinking Entertainment-Education for Development and Social Change; 12: Storytelling for Social Change; 13: Theater for Social Change; 14: Media Development; 15: Economics and Communication for Development and Social Change; 16: Peace Communication for Social Change: Dealing with Violent Conflict; 17: Social and Behavior Change Communication; 18: A Participatory Framework for Researching and Evaluating Communication for Development and Social Change; 19: Emerging Issues in Strategic Communication for Development and Social Change; Part III: Activist Approaches for Development and Social Change; 20: Social Movement Media in the Process of Constructive Social Change; 21: Transnational Civil Society and Social Movements; 22: Communication for Transparency and Social Accountability; 23: Citizens' Journalism: Shifting Public Spheres from Elites to Citizens; 24: Citizen's Media: Citizen's Watchdog Groups and Observatories; 25: Community Radio; 26: Youth-Generated Media; 27: Video for Change; 28: Emerging Issues in Activism and Social Change Communication; Index
UP System perpetual contents
Description based upon print version of record
Includes bibliographical references and index
Keywords: Communication in social action; Social change; Communication -- Social aspects; Mass media -- Social aspects